Radiological Spinal Canal Diameter as a Predictor of Surgical Outcome in Lumbar Canal Stenosis - Irfan Adil; Dr. Adeel-ur-Rehman; Ahmad, Toseef; Irum, Dr. Rafia; Adeel, Dr. Muhammad; Shaikh, Mohammad Faheem; Munir, Dr. Kiran; Chaulagain, Dipak (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Lumbar canal stenosis (LCS) is a degenerative disorder that is a frequent cause of neurogenic claudication and functional impairment. Radiological evaluation of the patient preoperatively might be an indicator of success in the surgery, especially the spinal canal diameter. Objective: To assess the importance of the radiological spinal canal diameter as one of the predictors of postoperative outcomes in patients on lumbar decompression surgery. Methods: The study was done as a cross-sectional study at Neurosurgery and Radiology Department of Punjab Institute of Neuroscience, Lahore from December 2024 to May 2025. 196 patients with confirmed degenerative LCS. Preoperative MRI was carried out on patients to measure the anteroposterior spinal canal diameter. The evaluation of postoperative outcomes was done by the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). The Chi-square tests were used to analyze the data with the help of SPSS 24. Results: The median canal diameter was 9.8 ± 1.6 mm. Surgical success (minimal improvement in ODI of at least 50% percent) occurred in 77.6% of the patients. The canal diameters were found to be significantly related to the postsurgery pain and worse functional recovery (p < 0.001). The patients with mild stenosis had better success in surgery (86.2%), moderate (78.4%), and severe (63.4%) stenosis. Conclusion: Preoperative spinal canal is an important predictor of the outcome of surgery in LCS. Proper radiological evaluation will help in surgical planning, better patient counseling, and higher recovery post-surgery.